2020
DOI: 10.1101/2020.01.13.904953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obesity-linked PPARγ S273 phosphorylation promotes insulin resistance through Growth Differentiation Factor 3

Abstract: Overnutrition and obesity promote adipose tissue dysfunction, often leading to systemic insulin resistance. The thiazolidinediones (TZDs) are a potent class of insulin-sensitizing drugs and ligands of PPAR that improve insulin sensitivity, but their use is limited due to significant side effects. Recently, we demonstrated a mechanism by which TZDs improve insulin sensitivity distinct from receptor agonism and adipogenesis: reversal of obesity-linked phosphorylation of PPAR at Serine 273. However, the role of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 67 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…This is in agreement with results from our group and others showing effects of GDF-3 ablation on weight gain only under situations of nutrient overload [25,109]. Hall et al [100] also showed that viral mediated overexpression of GDF-3 in adipose tissue reduced insulin sensitivity, but did not affect body weight in normal Chow diet, which is in line with previous GDF-3 overexpression studies [108]. Looking for a signaling mechanism of GDF-3 action, Hall et al tested GDF-3 activities in HEK293 (human kidney fibroblasts) and C2C12 (mouse myoblast) cell lines, but failed to observe activation of Smad2 and Smad3, effectors of the canonical signaling pathway activated by ALK4 and ALK7 receptors.…”
Section: Alk7 Ligands In Adipose Tissue Function and Homeostasissupporting
confidence: 94%
See 4 more Smart Citations
“…This is in agreement with results from our group and others showing effects of GDF-3 ablation on weight gain only under situations of nutrient overload [25,109]. Hall et al [100] also showed that viral mediated overexpression of GDF-3 in adipose tissue reduced insulin sensitivity, but did not affect body weight in normal Chow diet, which is in line with previous GDF-3 overexpression studies [108]. Looking for a signaling mechanism of GDF-3 action, Hall et al tested GDF-3 activities in HEK293 (human kidney fibroblasts) and C2C12 (mouse myoblast) cell lines, but failed to observe activation of Smad2 and Smad3, effectors of the canonical signaling pathway activated by ALK4 and ALK7 receptors.…”
Section: Alk7 Ligands In Adipose Tissue Function and Homeostasissupporting
confidence: 94%
“…Also, given the hyperinsulinemia of mice with a global inactivation of ALK7 signaling [38], attributing the enhanced lipolysis in ALK7-deficient mice to effects of insulin on GDF-3 expression may be problematic. Finally, a more recent report by Hall et al [100] found GDF-3 expression to be downregulated by 60% in adipose tissue macrophages of knock-in mice lacking phosphorylation at serine 273 of PPARc. The mutant mice displayed improved insulin sensitivity, mimicking some of the effects of PPARc agonists, such as thiazolidinedione compounds [111], but showed no differences from wild-type mice in body weight when fed on a Chow diet.…”
Section: Alk7 Ligands In Adipose Tissue Function and Homeostasismentioning
confidence: 88%
See 3 more Smart Citations